The role for endobronchial biopsy in the era of endobronchial ultrasound guided transbronchial needle aspiration for the diagnosis of sarcoidosis: a single center experience: Role for EBUS in the diagnosis of sarcoidosis - Cho, Roy; Pandey, Vidhay; Wong, Jennifer; Keenan, Joseph; Dincer, Erhan; Racila, Emilian; Allen, Tadashi; Perlman, David; Bhargava, Maneesh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Endobronchial biopsy (EBBX) has been reported to increase diagnostic yield for pulmonary sarcoidosis. The purpose of this study is to investigate the diagnostic yield for EBBX following endobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA). Methods: We identified a cohort of patients in the University of Minnesota Sarcoidosis Registry who had EBBx and EBUS-TBNA as part of workup for abnormal chest imaging. Data regarding demographics, biopsy approach and technique were recorded. Results: Our cohort included 37 patients (53.24±9.5, Male, 22±0.57; 3.8% were African American). In these patients who had EBBX, EBUS-TBNA was performed in 100% of patients and TBBX was performed in 2 patients (5%). EBBX was positive in 9 patients (24%) and EBUS-TBNA was positive in 34 patients (92%). TBBX was diagnostic in one of two patients. EBBX was the only diagnostic tissue in 3 of the 37 patients (8%). Conclusion: The diagnostic yield of EBBX is lower than previously reported, with only 8% of EBBXs demonstrating granulomatous inflammation. However, instrumentation used for obtaining EBBX as well as the presence of visible lesions does influence the diagnostic yield. Studies with adequate power are needed before implementing changes in clinical practice. When performed alongside EBUS-TBNA, EBBX did not significantly add to the diagnostic yield in sarcoidosis unless visible lesions were observed.